Communication Ethics of Da'i in Delivering Da'wah in Rantauprapat City - Tukino Tukino; Ahmad Tamrin Sikumbang; Zainun Zainun (Budapest International Research and Critics University, 2021)
This study aims to analyze the communication ethics of preachers in the delivery of da'wah and to analyze the challenges of communication ethics of preachers in the delivery of da'wah in Rantau Prapat City. The methodology used in this study are; a qualitative approach of the type of field research (field research) which is descriptive. With primary and secondary data sources. As well as data collection techniques through interviews (interviews) with 5 (five) Da'i and 5 (five) Mad'u informants, observation and documentation. The collected data is then analyzed using the theory of Miles and Huberman, namely reduction, presentation and verification of data so that a conclusion can be drawn. The results showed that; communication ethics in delivering da'wah in Rantau Prapat is based on the principles of Islamic communication based on the Qur'an and Hadith. In the implementation of the ethics of da'wah communication carried out by the da'i in the City of Rantau Prapat it is based on the communication values taught in Islam, such as the norm of honesty, upholding good manners, showing noble character and being polite to the audience by starting greetings, convey messages politely, set a noble example, give good advice, be fair, work on all messages conveyed, provide valid information, be responsible for the da'wah message conveyed and throw criticism and appropriate solutions. Based on the specific findings in this study, it shows that there are challenges faced by the da'i in implementing the ethics of da'wah communication in the City of Rantau Prapat such as; location of da'wah, advice on da'wah infrastructure, communicative congregations, lack of human resources in the field of da'wah, weather, and time.